Budaya Penerapan Sistem Literasi Morning Reading Pada Anak Sekolah di Era Digital - Amri, Farhan Hasinul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research is motivated by developments in increasingly sophisticated times that cause students who are still in school to become addicted to technology, usually called gadgets, who ultimately choose to play with technology rather than reading books or literacy. This research aims to describe the implementation of literacy culture in the digital era and identify supporting and inhibiting factors for literacy culture in order to increase students' interest in reading and writing. This research uses a descriptive qualitative approach. The results of this research are the implementation of the morning reading system in most schools in the city of Jember. Before starting teaching and learning activities, students are asked to read a book for 15-30 minutes, after that students are asked to analyze and evaluate what they have read and write on a piece of paper which will later be submitted to the teacher.